2010
DOI: 10.1111/j.1365-2672.2009.04429.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic mechanisms of retigeric acid B and azoles against Candida albicans

Abstract: Aims:  To clarify the underlying synergistic antifungal mechanisms of retigeric acid B (RAB) in combination with azoles against Candida albicans. Methods and Results:  Increased accumulation of rhodamine 123 in C. albicans was measured by both spectrophotometric method and flow cytometry. The inhibitory properties to the drug efflux of C. albicans were determined spectrophotometrically. The decreased cellular ergosterol synthesis was measured using its unique spectrophotometric absorbance profile, and the down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 21 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…[22][23][24][25] Specifically, our previous study found RAB displayed a synergistic action with azoles against the growth of C. albicans. 11) In the study, we compared the effects of the RAB-azole combination treatment to mono-drug therapy on hyphae formation. Our results showed that the treatment with RAB-azoles combination blocked the yeast-to-hyphal transition in C. albicans in vitro, while cells under mono-drug therapy grew mainly in hyphae or pseudohyphae form (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[22][23][24][25] Specifically, our previous study found RAB displayed a synergistic action with azoles against the growth of C. albicans. 11) In the study, we compared the effects of the RAB-azole combination treatment to mono-drug therapy on hyphae formation. Our results showed that the treatment with RAB-azoles combination blocked the yeast-to-hyphal transition in C. albicans in vitro, while cells under mono-drug therapy grew mainly in hyphae or pseudohyphae form (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Strains and Media C. albicans isolates YEM30, SC5314, CA2, 11) CA10 11) and CASA1 with green fluorescent protein (GFP) tagged CDR1 12) were used in this study and stored in culture medium supplemented with 10% (v/v) glycerol at −80°C. The isolates were propagated in YPD medium plates containing 2% agar at 30°C, inoculated into liquid YPD medium (2% tryptone, 1% yeast extract, 2% glucose) and incubated overnight in an orbital shaker (100 rpm) at 30°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations